A Tripartite Interaction Among the Calcium Channel α1- and β-Subunits and F-Actin Increases the Readily Releasable Pool of Vesicles and Its Recovery After Depletion - Gustavo A. Guzman; Raul E. Guzman; Nadine Jordan; Patricia Hidalgo; Patricia Hidalgo (Frontiers in Cellular Neuroscience, 2019)
Neurotransmitter release is initiated by the influx of Ca2+via voltage-gated calcium channels. The accessory β-subunit (CaVβ) of these channels shapes synaptic transmission by associating with the pore-forming subunit (CaVα1) and up-regulating presynaptic calcium currents. Besides CaVα1, CaVβ interacts with several partners including actin filaments (F-actin). These filaments are known to associate with synaptic vesicles (SVs) at the presynaptic terminals and support their translocation within different pools, but the role of CaVβ/F-actin association on synaptic transmission has not yet been explored. We here study how CaVβ4, the major calcium channel β isoform in mamalian brain, modifies synaptic transmission in concert with F-actin in cultured hippocampal neurons. We analyzed the effect of exogenous CaVβ4 before and after pharmacological disruption of the actin cytoskeleton and dissected calcium channel-dependent and -independent functions by comparing the effects of the wild-type subunit with the one bearing a double mutation that impairs binding to CaVα1. We found that exogenously expressed wild-type CaVβ4 enhances spontaneous and depolarization-evoked excitatory postsynaptic currents (EPSCs) without altering synaptogenesis. CaVβ4 increases the size of the readily releasable pool (RRP) of SVs at resting conditions and accelerates their recovery after depletion. The enhanced neurotransmitter release induced by CaVβ4 is abolished upon disruption of the actin cytoskeleton. The CaVα1 association-deficient CaVβ4 mutant associates with actin filaments, but neither alters postsynaptic responses nor the time course of the RRP recovery. Furthermore, this mutant protein preserves the ability to increase the RRP size. These results indicate that the interplay between CaVβ4 and F-actin also support the recruitment of SVs to the RRP in a CaVα1-independent manner. Our studies show an emerging role of CaVβ in determining SV maturation toward the priming state and its replenishment after release. We envision that this subunit plays a role in coupling exocytosis to endocytosis during the vesicle cycle.